Revealing the Orientation of the Post-Reformation Islamic Student Movement in Indonesia - Ahmad Izudin (Politika: Jurnal Ilmu Politik, 2021)
This article explains the traces of the post-reformation Islamic student movement. The movement is still considered as the power of civil society to conduct democratization, but its tendency does not lead to social transformation. Sidney Tarrow (1996) used a theory of collective behavior reference in social movements to discuss this issue. This article is based on a qualitative research method. The data were collected by using Focus Group Discussion, interview, documentation, and literature review. This study finds out that an orientation shifting of the Islamic student movement, which is interesting to reveal. The shifting indicates the tendency to change orientation accordingly to the national political change and fluctuations. In this situation, the Islamic student movement has experienced several social dynamics. A new movement model arises when they use social media as an alternate formto convey their social criticism like through the street demonstration to critize governance practices.